A Scientometric Analysis of Global Trends in Research Data Management Practices - Dash, Manoranjan; Cheshta; Prabhu, Sushmitha; Kapila, Ish; Khilla, Gananath (Indian Journal of Information Sources and Services, 2025)
Aim: Research Data Management (RDM) has developed as a critical field of scholarly attention in response to the rising significance of data-intensive research, open art initiatives, and the evolving demands of data stewardship. Methodology: This theoretical investigation presents an inclusive scientometric examination of global trends, patterns, and thematic developments in RDM research from 2015 to 2024. Drawing data from the Web of Science (WoS) and Scopus databases, this research employed quantitative techniques using tools, such as VOSviewer and Bibliometrics (R-package) to analyze publication volume, citation impact, co-authorship networks, country and institutional contributions, and keyword co-occurrence mapping. Result: The results indicate a substantial increase in RDMrelated publications, particularly after 2015, which is aligned with the proliferation of FAIR data principles and mandates by funding bodies. Thematic clustering revealed key focus areas, including data-sharing policies, metadata standards, digital curation, data repositories, and institutional strategies for research data services. Furthermore, the analysis highlights a shift toward interdisciplinary approaches, involving domains, such as data science, computer science, library science, and health sciences. Conclusion: This scientometric evaluation provides a foundational understanding of the intellectual and collaborative structure of RDM research, offering actionable insights for researchers, data professionals, and policymakers aiming to enhance research data infrastructure and governance on a global scale.